PENGEMBANGAN POSTER MEDIA TANAM JAMUR TIRAM AMPAS KELAPA DAN PELEPAH KELAPA SAWIT PADA PEMBELAJARAN BIOLOGI SMA KELAS X (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Poster is one of the image-based learning media that contains the latest innovations. This study aims to produce a poster design of coconut dregs and oil palm fronds as growing media for oyster mushrooms in class X high school biology learning. This research was conducted in July – September 2021 at the Biology Education Mushroom House and Laboratory of PMIPA FKIP Riau University. The design of this poster refers to the ADDIE development model. At the analysis stage, the curriculum, materials and posters were analyzed beforehand. At this stage, an analysis of the 2013 revised 2018 curriculum will be carried out on the Biology material for class X SMA issued by the Ministry of National Education based on the related material learning program activity plan. The analysis aims to determine the syllabus, lesson plans, and materials that are suitable for use and are made as learning media that are adapted to KI and KD. The design stage is done by designing learning tools and designing posters. The process of making poster media starts from compiling a framework with content made elongated with 2 types of sizes, namely 90 X 60 cm, and A4 paper size 29.5 X 21 cm. Based on the results of analysis, design and development, research results can be serve as a source of learning in the form of learning posters on the material of environmental change and pollution class X SMA KD 3.6 and 4.6.Key Words: Poster, Learning Media, ADDIE, Oyster Mushroom